Implementation of Virtual Reality for Photography Exhibitions - Rizky Syahputra Setyawan; M Mahaputra Hidayat; Lutfia Febrianti; Moch Alif Firmansyah (JEECS (Journal of Electrical Engineering and Computer Sciences), 2023)
Art exhibitions are one way to communicate a work of art while displaying creations that can be enjoyed by visitors. However, it takes a very high cost to make a good exhibition hall, and many people are too lazy to go to the exhibition if it is just to look around. In this era of technology 4.0, many new innovations have emerged in human life, one of which is virtual reality. Virtual reality is increasingly being used as an alternative to visiting a place without having to come there directly. This research aims to create an Android system using virtual reality that provides an experience to users viewing works virtually. Virtual reality prepares a representative space to display works and also does not need to incur high costs while still providing quality and complete information from exhibition speakers. This research was built using Blender and Unity.  In the application design analysis, there are four main stages: (1) analysis, (2) design, (3) product development, and (4) product testing. The results of the assessment conducted by the virtual reality lecturer obtained an average result of 89%. In addition, the results of trials for students obtained an average percentage of 94% and were included in the very good category. The results of this study show that AR has indeed proven feasible to be used as a learning medium in introducing photographic works with 2D and 3D Animation, and therefore the potential to make exhibitions in VR is also used for other courses and learning. The result of this research is that an Android-based virtual reality system can simulate the exhibition of artwork.